Litsea cubeba (May Chang) Essential Oil의 Streptococcus mutans와 Porphyromonas gingivalis에 대한 항균효과 - 박충무; 윤현서 (한국구강보건과학회지, 2023)
Objectives: This study analyzed the antibacterial effects of Litsea cubeba essential oil (LCEO) against both Streptococcus mutans and Porphyromonas gingivalis, as well as inhibitory effect on biofilm formation. Methods: Antibacterial activity of LCEO was analyzed by minimum inhibition concentration on bacterial growth, disk diffusion and growth inhibitory assays. In addition, growth inhibitory effect of LCEO was also evaluated by biofilm formation assay. Results: LCEO significantly inhibited growth of S. mutans and P. gingivalis in a dose dependent manner. In addition, these results were coincided with the result of biofilm formation assay. Conclusions: LCEO exhibited potent antibacterial activity against both pathogens, which provides that LCEO might be used as a potential candidate for oral healthcare supplies. KCI Citation Count: 1